Beyond al-Qaeda. - Rabasa, Angel (Beyond al-Qaeda, 2006)
This book examines terrorist groups that, while not formally allied with al-Qaeda, pose a threat to Americans, at home and abroad, and to the security of our friends and allies. Although the temptation for policymakers is to set aside as less dangerous those groups that have not chosen to join al-Qaeda, such terrorist or insurgent groups and criminal organizations still pose a threat to the United States, its interests, and its allies. The authors first look at violent Islamist terrorist and insurgent groups without formal links to al-Qaeda, such as Hamas and Hezbollah in the Middle East and Islamist groups in Africa. They then examine a number of non-Islamist terrorist groups-for example, the Tamil Tigers in Sri Lanka, the FARC and ELN in Colombia, Maoist insurgencies, and the violent antiglobalist movement-and explain how these groups might fit into the al-Qaeda agenda and how they use criminal organizations and connections to finance their activities. Finally, they show how the presence of these threats affects U.S. security interests, and they identify distinct strategies that the United States may take to neutralize or mitigate each of them.